PENGELOLAAN LINGKUNGAN MELALUI PENGOLAHAN SAMPAH RUMAH TANGGA TERINTEGRASI - Utami, Bekti Wahyu; Mardikanto, Totok (Universitas Negeri Yogyakarta, 2016)
The purpose of community service is to (1) increase the awareness towards the environment; (2) improving the quality of life; and (3) improvelife peace and comfort. The method used is socialization, composting trainingand craft-making training busing household waste. The results of community service is the socienty's standard of living of as individuals and groups was improved through waste management business, the public awareness in saving the environment was increased. The quality of urban environment with waste management was increased through the applying of 3R (Reuse, Reduce and Recycle) and the society's cognitive and conative aspects were also improved regarding to the integrated waste management